Numerical modeling of thermal desorption mass spectroscopy (TDS) for the study of hydrogen diffusion and trapping interactions in metals. (2nd March 2015) - Hurley, Caitlin; Martin, Frantz; Marchetti, Loïc; Chêne, Jacques; Blanc, Christine; Andrieu, Eric
Abstract Deriving the kinetic reaction constants associated with hydrogen diffusion and trapping in metals from thermal desorption mass spectroscopy (TDS) spectra proves to be complicated and the existing analysis methods are subject to debate. This article will provide a brief background of several commonly employed analysis techniques and discuss the necessity of a more complex and rigorous analysis method for the determination of the kinetic constants associated with hydrogen trapping interactions. Furthermore, a numerical simulation method will be proposed using the McNabb & Foster equations to fit experimental TDS spectra in order to derive both diffusion and trapping/detrapping parameters, including the respective pre-exponential constants and activation energies associated with these interactions in metals.